HUBUNGAN INTER-SEMIOTIK TEKS VERBAL DAN VISUAL DALAM TARI SAMAN GAYO LUES - Ayu Yuniasari; T. Silvana Sinar; Nurlela . (BAHAS, 2018)
Relationship of Inter-semiotics Verbal and Visual Text on Saman Gayo Lues Dance. The aimed to describe the retationship of inter-semiotics verbal and visual text on Saman Gayo Lues dance. Source of the data was the recordings of Saman Gayo Lues danca which showed in Unsyiah Banda Aceh and interview result from the informant in Gayo Lues society. The data was analyzed by Inter-semiotics Logical Relations theory. The result showed that the retationship of inter-semiotics verbal and visual text on Saman Gayo Lues dance involve: repeating (8 senteces), comparative (1 sentence), additiv (3 sentences), and consequential (5 senteces). Keywords: Inter-semiotics, Verbal Text, Visual Text, Saman Gayo Lues Dance